Elevated soluble lectin-like oxidised low-density lipoprotein receptor-1 (sLOX-1) associated with increased risk for heart failure and MACE after an acute coronary event. (14th October 2021) - Schiopu, A; Svedlund, S; Yndigegn, T; Varma, V; Ongstad, E L; Collen, A; George, R T; Wang, X; Goncalves, I; Nilsson, J; Gan, L M
Abstract: Background/Introduction: The lectin-like oxidised low-density lipoprotein receptor (LOX-1) is involved in atherosclerotic plaque inflammation and vulnerability. Plasma levels of soluble LOX-1 (sLOX-1) have previously been associated with increased risk for recurrent coronary events and mortality in patients with acute coronary syndrome (ACS). Purpose: To assess the association of sLOX-1 with the development of heart failure (HF) post-ACS. Methods: We measured sLOX-1 in 524 patients with ACS within 24 hours after the acute event. A subgroup of 97 of these patients completed a follow-up echocardiogram after one year. The incidence of HF-related hospitalisation and recurrent major adverse cardiovascular events (MACE), defined as recurrent ACS or cardiovascular death, was followed for a mean period of two years. In a separate cohort of 363 patients with ACS and percutaneous coronary intervention (PCI), we studied the correlations between sLOX-1, coronary flow reserve, left ventricular systolic function and systemic inflammation at two follow-up visits within four weeks and 16 weeks post-ACS, respectively. Results: Baseline sLOX-1 was positively associated with the risk of HF and MACE, independently of traditional cardiovascular risk factors, revascularisation and medication. The hazard ratios and 95% confidence intervals were 1.57 (1.10–2.23), p=0.012 for HF and 1.36 (1.08–1.71), p=0.009 for MACE per standard deviation baseline sLOX-1 increase. Elevated sLOX-1 was also negatively associated with lower-left ventricular ejection fraction at one year (r=−0.263, p=0.009). In the second ACS cohort, we found that plasma sLOX-1 measured at the two follow-up visits was negatively associated with coronary flow reserve and left ventricular systolic function, and positively correlated with biomarkers of systemic inflammation and cardiac overload. Conclusion: Elevated sLOX-1 is associated with the development of HF and recurrent cardiovascular events in patients with ACS. Although this association study cannot confirm causality, the results suggest LOX-1 as a potential biomarker and treatment target in patients with ACS. FUNDunding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Swedish Research Council The Swedish Heart and Lung foundation Swedish Foundation for Strategic Research Dnr IRC15-0067 Marianne and Marcus Wallenberg Foundation Bundy Academy at Lund University